Nanocrystalline cerium oxide prepared from a carbonate precursor and its ability to breakdown biologically relevant organophosphates. Issue 6 (25th April 2017) - Janoš, Pavel; Henych, Jiří; Pfeifer, Jan; Zemanová, Nikola; Pilařová, Věra; Milde, David; Opletal, Tomáš; Tolasz, Jakub; Malý, Marek; Štengl, Václav
Abstract : The phosphatase-mimetic ability of nanocrystalline cerium oxide was demonstrated using thiamine pyrophosphate (TPP) and nicotinamide adenine dinucleotide (NAD) as model compounds. Abstract : The unusual ability of cerium oxide to cleave phosphoester bonds under relatively mild (ambient) conditions was demonstrated using thiamine pyrophosphate (TPP) and nicotinamide adenine dinucleotide (NAD) as model compounds. This phosphatase-mimetic ability can be exploited in biology or medicine, e.g., for protein design; however, it represents a potential threat to vital systems in living organisms, such as the phosphate backbone of DNA and RNA. The ability of cerium oxide to promote the cleavage of the bridging pyrophosphate group in the NAD molecule was examined for the first time; it was shown that the cleavage products differ markedly from the commonly observed products of enzymatic or non-enzymatic hydrolysis of NAD. This ability is highly specific for cerium oxide; it was not observed to a comparable extent with any of the other tested metal oxides (La2 O3, Nd2 O3, Pr6 O11, TiO2, manganese oxide and several iron oxides). The phosphatase-mimetic ability stems from the unique properties of cerium cations and may be related to measurable and, to some extent, adjustable characteristics, such as crystallinity, surface area, Ce 3+ /Ce 4+ ratio or the content of surface functional groups. The in-house prepared nanocrystalline cerium oxide exhibited a markedly higher phosphatase-mimetic ability than the commercial nanoceria. The interactions of the cerium oxide nanoparticles with TPP and NAD were also examined with the aid of molecular dynamics simulations.